Use of thermodynamic chemical potential diagrams (µCaO, µCO2) to understand the weathering of cement by a slightly carbonated water Uso de diagramas de potencial químico termodinâmico (µCaO, µCO2) para o entendimento da resistência do cimento à água levemente carbonatada - A. Blandine; G. Bernard; B. Essaïd (Cerâmica, 2008)
Cement is a ubiquitous material that may suffer hazardous weathering. The chemical weathering of cement in natural environment is mostly characterized by the leaching of CaO and the addition of CO2. The different weathering zones that develop at the expense of the cement may be predicted by the help of chemical potential phase diagrams; these diagrams simulate the behaviour of systems open to some chemical elements. Some components have a so-called inert status, that is to say the system is closed for these components, their amount in the system remains constant; some other components have a mobile status, that is to say these components can be exchanged with the outside of the system, their amount can vary from one sample zone to another. The mobile components are represented in the model by their chemical potentials (linked to their concentrations) that are variable in the external environment. The main features of the weathering of a cement system open to CaO and CO2 are predicted in a phase diagram with µCaO et µCO2 as diagram axes. From core to rim, one observes the disappearance of portlandite, ettringite and calcium monosulfoaluminate, the precipitation of calcite and amorphous silica, the modification of the composition of the CSH minerals (hydrated calcium silicates) that see a decrease of their c/s ratio (CaO/SiO2) from the core to the rim of the sample. For the CSH minerals, we have separated their continuous solid solution into three compositions defined by different CaO/SiO2 ratios and called phases 1, 2 and 3: CaO = 0.8, 1.1, 1.8 respectively for one mole of SiO2 knowing that H2O varies in the three compositions. Cimento é um material de ampla utilização que pode ser sujeito a modificação pelo tempo. A modificação química do cimento em meio natural é principalmente caracterizada por lixiviação de CaO e adição de CO2. As diferentes zonas de resistência que se desenvolvem às custas do cimento podem ser previstas com os diagramas de fase do potencial químico; estes diagramas simulam o comportamento de sistemas abertos a alguns elementos químicos. Alguns componentes têm o chamado status inerte, significando que o sistema é fechado para estes componentes, seu teor no sistema permanece constante; alguns outros componentes tem um status móvel, significando que estes componentes podem ser trocados com o meio exterior, seu teor podendo variar de uma região da amostra para outra. Os componentes móveis são representados no modelo pelos potenciais químicos (ligados às suas concentrações) que variam no meio exterior. Os principais aspectos da resistência ao tempo de um sistema cementício aberto a CaO e CO2 são previstos em um diagrama de fases com µCaO e µCO2 como eixos do diagrama. Do centro para a extremidade observa-se o desaparecimento de portlandita, ettringita e monosulfoaluminato de cálcio, a precipitação de calcita e sílica amorfa, a modificação da composição de minerais CSH (silicatos de cálcio hidratados) que tem o decréscimo da razão c/s (CaO/SiO2) do centro para a extremidade da amostra. Para os minerais CSH, forma separadas as soluções sólidas contínuas em três composições definidas por diferentes razões CaO/SiO2, denominadas fases 1, 2 e 3: CaO = 0,8, 1,1, 1,8, respectivamente para 1 mol SiO2 sabendo que H2O varia nas três composições.